Upgrading and repairing servers - Mueller, Scott (Upgrading and Repairing Ser., 2006)
As the price of servers comes down to the level of desktop PCs, many small - and medium-sized businesses are forced to provide their own server setup, maintenance and support, without the high-dollar training enjoyed by their big corporation counterparts. This book is the first line of defense for small- and medium-sized businesses, and an excellent go-to reference for experienced administrators who have pined for such a reference! It's all here in one, incredibly useful tome that readers will refer to again and again. Weighing in at more than 1,400 pages, this book blows away the competition's attempts to cover server hardware.